Microstructures in the hinge plate of the studied Arctica islandica specimens. - Nils Höche (10204233); Eric O. Walliser (10204236); Niels J. de Winter (3358778); Rob Witbaard (549727); Bernd R. Schöne (8187015) (2021)
(A) Hinge portions formed in the Baltic Sea predominantly exhibited crossed-acicular (CA) microstructure. Annual growth lines (black line) consisted of irregular simple prisms (ISP), often followed by 10–20 μm-broad fine complex crossed-lamellar (FCCL) fringes, as shown here. Numerous faintly visible disturbance lines (red line) consisted of fibrous prismatic (FP) or spherulitic prismatic (SphP) microstructures. (B) Magnified image of the CA microstructures formed in the Baltic Sea. BMUs consist of a few elongated crystallites, which merged with each other and were loosely aligned in two predominant directions (open angles in direction of growth). (C) Microstructures of shell portions formed in the Baltic Sea (B.S.; leftmost image portion) and the early acclimatization phase (rightmost image portion). A prominent disturbance line (red) composed of SphP microstructure delimits the two shell portions. During the acclimatization phase, FCCL microstructures were produced. (D) Magnified image of the FCCL microstructures formed during the acclimatization phase. Compared to CA microstructures, the FCCL BMUs are even more elongated, strictly aligned in two dip directions and intersect with their neighboring units. (E-F) The CA microstructures formed under controlled temperature in the laboratory exhibited a rather uniform appearance along the growth axis. Dip directions of the needle shaped BMUs varied more strongly than those formed in the Baltic Sea, leading to a looser arrangement and a less organized appearance. All microstructures–except ISP–contained nm- to μm-sized pores (yellow arrows). Black arrows indicate direction of growth.